(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of Phenylephrine combined with continuous intravenous infusion of Noradrenaline in treating hypotension in patients with severe traumatic brain injury undergoing emergency surgery. Methods: The study analyzed articles searched on the electronic databases PubMed, Journals, Neurosurgery, Journal of Critical Care, showing that the combination of Phenylephrine and continuous intravenous infusion of Noradrenaline would be a good choice in anesthesia and resuscitation of patients with severe traumatic brain injury... The combination of Phenylephrine and Noradrenaline increases mean arterial blood pressure, increases cerebral perfusion pressure, thereby improving treatment outcomes for patients with severe traumatic brain injury. Results: Phenylephrine is an α-adrenergic agonist that increases systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure. Phenylephrine combined with Noradrenaline is a sympathomimetic agonist that acts on both α1-adrenergic receptors and β1-adrenergic receptors, causing vasoconstriction and hypertension, ensuring maintenance of cerebral perfusion pressure in severe traumatic brain injury, reducing the dose of Noradrenaline or Phenylephrine if used alone, reducing treatment costs for patients, but further clinical research is still needed. Conclusion: Phenylephrine combined with Noradrenaline has vasoconstrictor and blood pressure increasing effects, ensuring maintenance of cerebral perfusion pressure in severe traumatic brain injury.